Impacts of Government Policies, Technological Innovation, and Competitive Advantage on Post Pandemic MSME Financial - Evi Maulida Yanti; Boihaki; Fatmayanti; Denni (Business Review and Case Studies, 2024)
The aim of this research was to analyze the role of government, technological innovation, competitive advantage, and financial institutions in the performance of MSMEs post-pandemic. This research was quantitative research. The data processing used in the research was SmartPLS. This research was conducted in Aceh Province, where 200 MSME managers were selected as samples. The results of this research showed that the role of government had a negative effect on the performance of MSMEs, technological innovation had a positive effect on the performance of MSMEs, competitive advantage had a positive effect on the performance of MSMEs, the role of government had a negative effect on financial institutions, technological innovation had a positive effect on financial institutions, competitive advantage had a negative effect on financial institutions, financial institutions had a negative influence on the performance of MSMEs, financial institutions mediated the role of government on the performance of MSMEs, financial institutions mediated innovation technology on the performance of MSMEs, and financial institutions mediated competitive advantage on the performance of MSMEs. This meant that MSMEs needed to continue improving innovation technology and competitive advantage through financial institutions and the role of government in supporting MSME performance. Innovation technology and competitive advantage needed to be improved in achieving maximum MSME performance in the current technological era because technological civilization was increasingly developing. Keywords: role of government, innovation technology, competitive advantage, financial firm, msme performance